Immobilizing Bactericides on Dental Resins via Electron Beam Irradiation. (September 2021) - Thongthai, P.; Kitagawa, H.; Iwasaki, Y.; Noree, S.; Kitagawa, R.; Imazato, S.
Polymerizable bactericides, such as quaternary ammonium compound–based monomers, have been intensively studied as candidates for immobilizing antibacterial components on dental resin. However, they predominantly exhibit a bacteriostatic behavior, rather than bactericidal, as the immobilized components are left with insufficient molecular movement to disrupt the bacterial surface structure through contact-mediated action. In this study, we developed a novel strategy to increase the density of the immobilized bactericide and enhance its antibacterial/antibiofilm properties by combining a surface-grafting technique with electron beam irradiation. A solution of the quaternary ammonium compound–based monomer, 12-methacryloyloxydodecylpyridinium bromide (MDPB), was coated on polymethyl methacrylate (PMMA) resin specimens at the concentrations of 30, 50, and 80 wt%. The coated resins were subsequently exposed to 10 MeV of electron beam irradiation at 50 and 100 kGy, followed by thermal stabilization at 60 °C. The antibacterial effect was evaluated by inoculating a Streptococcus mutans suspension on the coated PMMA resin samples, which exhibited bactericidal effects even after 28 d of aging ( P < 0.05, Tukey's honestly significant difference test). Transmission electron microscopy and bacteriolytic activity evaluation revealed that the S. mutans cells had sustained membrane depolarization. Furthermore, the antibiofilm effects against S. mutans and bacteria collected from human saliva were assessed. The thickness and the percentage of membrane-intact cells of the S. mutans and multispecies biofilms formed on the MDPB-immobilized surfaces were significantly lower than the uncoated PMMA specimens, even after 28-d aging ( P < 0.05, Tukey's honestly significant difference test). Thus, the immobilization of antibacterial MDPB via electron beam irradiation induced rapid membrane depolarization, increasing membrane permeability and eventually causing cell death. Our strategy substantially enhances the antibacterial properties of the resinous materials and inhibits biofilm formation, therefore demonstrating significant potential for preventing infectious diseases in the oral environment.